Physiological traits associated with yield performance of spring wheat (Triticum aestivum ) under late-sown conditions - NAGARAJAN, SHANTHA; JAGADISHRANE, JAGADISHRANE (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted for 2 crop seasons (1997-98 and 1998-99) with 12 diverse genotypes of wheat (Triticum aestivum L. emend. Fiori & Paol.), to understand the genetic variation in physiological growth and yield parameters under timely and late-sown conditions. Association between these characters and grain yield was also studied to identify physiological traits for selecting genotypes tolerant to late heat condition. All traits measured showed reduction under late sowing with the exception of harvest index, which registered an increase. Barring days to antbesis and grain-growth duration, all other growth parameters, viz spike number, and biomass/m2, and yield parameters, viz grain number and weight/spike, harvest index, grair-growth rate showed good variability (high CV) and significant correlation with yield under late-sown condition. In late-sown crop, canopy temperature depression measured after anthcsis showed significant correlation with grain yield (r= 0.0.681, P= 0.01). High correlation between yields of normal and late sowings (r = 0.879, P=0.01) indicated that superior genotypes perfomled well under late-sown condition by virtue of their high yield potential rather than stress tolerance.